Combination of Zadek Osteotomy and Achilles Tendon Re-Attachment in Severe Haglund Deformity: A Case Report - Kevin Kusuman; I Wayan Subawa; Mohamad Dimas Ismail (GLOBAL HEALTH SCIENCE GROUP, 2025)
Haglund deformity refers to a bony exostosis on the posterosuperior aspect of the calcaneus, often causing retrocalcaneal bursitis and Achilles tendinopathy. Conservative treatments, including physiotherapy and medication, may not relieve symptoms in severe cases. Surgical intervention is indicated when non-operative treatments fail. This report highlights a case of severe Haglund deformity managed with Zadek osteotomy and Achilles tendon re-attachment.Case Presentation: A 45-year-old female presented with 2 months of severe right heel pain and a 2-year history of a prominent bump. Physical therapy yielded no improvement. Clinical and radiographic evaluation confirmed Haglund deformity with insertional Achilles tendinopathy. Surgical treatment involved Zadek osteotomy, fixation with screws, and Achilles tendon re-attachment using a suture anchor. The combined approach addressed both the bony deformity and tendon degeneration. Post-operative outcomes showed significant improvement. At the 3-month follow-up, the patients Visual Analog Scale (VAS) pain score decreased from 7/10 to 1/10, and the American Orthopaedic Foot & Ankle Society (AOFAS) Ankle-Hindfoot score improved from 55 to 90. The range of motion was near normal, and functional recovery was excellent. This case demonstrates the effectiveness of combining Zadek osteotomy and Achilles tendon re-attachment for treating severe Haglund deformity. This approach provided significant pain relief and functional recovery, making it a viable option for patients with similar conditions refractory to conservative management.